2021
DOI: 10.1177/03128962211009578
|View full text |Cite
|
Sign up to set email alerts
|

Governing information technology (IT) investment: A contingency perspective on organization’s IT investment goals

Abstract: Using contingency theory, we argue that there is not a uniform approach for companies to govern information technology (IT) investments. Rather, the level of governance over IT investments is contingent upon the organization’s goals for its IT investments. We find that Australian organizations with both operation- and market-focused IT investment goals (i.e. dual-focused IT goals) demonstrate higher IT investment governance (ITIG) levels than those with less focused IT goals. We also document that dual-IT-focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Different IT strategic goals lead to different levels of IT investment. Namely, organizations with operational and market-oriented IT investment goals have higher IT investment levels than those that do not pay much attention to IT investment goals [16]. RFID investments aimed at reducing corporate management deficiencies can have a considerable impact on productivity gains [17].…”
Section: Rfid Investment From the Perspective Of Dctmentioning
confidence: 99%
“…Different IT strategic goals lead to different levels of IT investment. Namely, organizations with operational and market-oriented IT investment goals have higher IT investment levels than those that do not pay much attention to IT investment goals [16]. RFID investments aimed at reducing corporate management deficiencies can have a considerable impact on productivity gains [17].…”
Section: Rfid Investment From the Perspective Of Dctmentioning
confidence: 99%
“…The ideal condition is that the increasing population of HNWI leads to an increase in the state revenue from will provide benefits as planned by the organizations. In sum, effective governance is crucial for facilitating and conveying business value (Ali et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve organizational goals, IT in an organization is not enough if it is only regulated, but IT must be managed professionally. Earlier studies found that many organizations have taken note of the concept of IT governance (ITG) in order to justify IT investments ( Mikalef et al, 2021 ; Ali et al, 2022 ). Because ITG can balance the interests of all parties and enables IT investments to be effective, the matching of IT goals and enterprise goals is a part of corporate governance ( Simonsson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%